Quality and yield of Ricotta cheese as affected by milk fat content and coagulant type - Ortiz Araque, Leidy Carolina (2018)
Milk processing conditions can exert a large influence on the quality of acid-coagulated cheeses. Herein, we evaluated the influence of milk fat content and coagulant type on Ricotta yield and physical, chemical and sensory properties. Fat-free Ricotta was hard and whiter than reduced-fat or full-fat Ricotta. Ricotta produced from low-fat and whole milk showed no differences in acceptability, indicating that fat content could be substantially reduced without impairing quality. Milk coagulation by citric acid decreased Ricotta moisture, firmness and yield, whereas calcium chloride produced a white Ricotta with desired firmness and high consumer acceptability.